This article presents a reflective analysis of the temporal dimension in education, based on transcripts of school ethnographies conducted in seven schools in Valencia between 2017 and 2020. Through a re-examination of field notes written by university students, it examines how the organization, management, and experience of school time shape a disciplinary system that unequally impacts the well-being, health, and educational trajectories of students. The study identifies time as an element of structural violence and a constitutive characteristic of the school institution. The findings reveal the internal reality of classrooms, where the school climate and instructional time are eroded by outdated pedagogies, relationships that prioritize domination, coordination failures, and tedious tasks. Furthermore, it demonstrates how the rigid management of schedules and the outsourcing of tasks (homework) deepen social inequalities and penalize students with fewer resources. In conclusion, the work highlights that schools operate under the logic of totalitarian institutions that ignore the needs of children. - Gabaldón Estevan, Daniel (Sociedad e Infancias, 2026)
Este artigo apresenta uma análise reflexiva da dimensão temporal na educação, baseada em transcrições de etnografias escolares realizadas em sete escolas de Valência entre 2017 e 2020. Através de uma reavaliação de notas de campo escritas por estudantes universitários, o estudo identifica o tempo como um elemento de violência estrutural e uma característica constitutiva da instituição escolar. Os resultados revelam a realidade interna das salas de aula, onde o clima escolar e o tempo de instrução são corroídos por pedagogias ultrapassadas, relações que priorizam a dominação, falhas de coordenação e tarefas fastidiosas. Além disso, demonstra como a gestão rígida dos horários e a externalização de tarefas (trabalhos de casa) aprofundam as desigualdades sociais e penalizam os alunos com menos recursos. Em conclusão, o trabalho realça que as escolas operam sob a lógica de instituições totalitárias que ignoram as necessidades das crianças.